2015
DOI: 10.1039/c5an00622h
|View full text |Cite
|
Sign up to set email alerts
|

Facile and controllable synthesis of hydroxyapatite/graphene hybrid materials with enhanced sensing performance towards ammonia

Abstract: In this work, needle-like and micro-spherical agglomerates of nanocrystalline hydroxyapatite (HA) were successfully assembled on the surface of graphene sheets with the aid of dopamine having two roles, as a template and a reductant for graphite oxide during the process of self-polymerization. The crystalline structure and micromorphology of HA can be conveniently regulated by controlling the mineralization route either with a precipitation (cHA/GR) or biomimetic methodology (bHA/GR). Both the composites exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 52 publications
1
27
0
1
Order By: Relevance
“…On the other hand, the angle between (211) and (300) planes in HA was about 27 degrees. Therefore, the rGO surface was tangible to the HA (300) planes [46,47]. By comparing FFT analyzes ( figure 7(h)), it is found that rGO cross section analysis was galactic.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, the angle between (211) and (300) planes in HA was about 27 degrees. Therefore, the rGO surface was tangible to the HA (300) planes [46,47]. By comparing FFT analyzes ( figure 7(h)), it is found that rGO cross section analysis was galactic.…”
Section: Resultsmentioning
confidence: 96%
“…This composite presented an excellent in vitro biomineralization after soaking in SBF. In other studied too, HAp was deposited on graphene sheets [534], GO sheets [535], or functionalized graphene nanosheets [536,537,538]. Usually, the nanocomposites are synthesized as nanoparticles in solutions and should be separated by centrifugation.…”
Section: Composite Calcium Phosphatesmentioning
confidence: 99%
“…In addition to these applications, the specific characteristics of HAP, such as low water solubility and high stability under oxidising and reducing conditions, make this material suitable as a sorbent in the purification of wastewater and removal of a variety of heavy metals, such as arsenic (III), selenium (IV), lead (II), cadmium (II), cobalt (II) or nickel (II) from contaminated industrial aqueous waste [5][6][7][8][9]. Another powerful application of HAP is the determination of ammonia for applications such as environmental pollution control, reported by Zhang et al [10], who describe electrochemical detection of ammonia (at room temperature) using a composite of HAP/graphene which exhibits a significant improvement in the analytical sensitivity compared to that of a bare graphene sensor. Furthermore, Kanchana et al [11] employed HAP towards the electrochemical detection of uric acid demonstrating a limit of detection of 142 nM, which was applied to human urine and blood serum.…”
Section: Introductionmentioning
confidence: 99%